2021
DOI: 10.3390/nu13103366
|View full text |Cite
|
Sign up to set email alerts
|

Can Assessing Physical Activity Liking Identify Opportunities to Promote Physical Activity Engagement and Healthy Dietary Behaviors?

Abstract: Improving our understanding of what physical activities are enjoyed and the factors that are associated with physical activity liking can promote participation in regular physical activity. We aimed to study physical activity (PA) liking in college women by modelling interactions between body size perception and dietary behaviors on PA liking, and by examining discrepancies between PA liking versus engagement on body size perception and dietary behaviors. Women (n = 251; 74% white) utilized an online survey to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…This online tailored message program utilized the IMB framework to adapt an evidence-based program, originally conducted with children their parents/caregivers [ 31 ] or children in a middle school setting [ 32 ], for college students. The program consisted of a validated survey assessing liking/disliking of usual diet and physical activity behaviors [ 46 , 82 , 83 ], questions assessing current health knowledge and behaviors [ 72 , 84 , 85 , 86 , 87 , 88 ], and tailored messages driven by response to the liking survey (food and physical activity), intuitive eating, stress, and sleep. Following the IMB framework, the program assessed knowledge/information of participants through: (1) baseline knowledge related to message Information and responses to each message; (2) reported Information learned; (3) Motivation on how much they would like to try/continue targeted behavior; and (4) Behavioral Skills by assessing confidence/self-efficacy to try/continue the targeted behavior.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This online tailored message program utilized the IMB framework to adapt an evidence-based program, originally conducted with children their parents/caregivers [ 31 ] or children in a middle school setting [ 32 ], for college students. The program consisted of a validated survey assessing liking/disliking of usual diet and physical activity behaviors [ 46 , 82 , 83 ], questions assessing current health knowledge and behaviors [ 72 , 84 , 85 , 86 , 87 , 88 ], and tailored messages driven by response to the liking survey (food and physical activity), intuitive eating, stress, and sleep. Following the IMB framework, the program assessed knowledge/information of participants through: (1) baseline knowledge related to message Information and responses to each message; (2) reported Information learned; (3) Motivation on how much they would like to try/continue targeted behavior; and (4) Behavioral Skills by assessing confidence/self-efficacy to try/continue the targeted behavior.…”
Section: Methodsmentioning
confidence: 99%
“…A proxy of physical activity and dietary behaviors was captured using a previously validated, online liking survey for college-aged individuals [ 46 , 82 , 83 ]. Each activity, food or beverage item was each shown as an image and text label to the left of a horizontal, hedonic scale with five faces and corresponding descriptors of “love it”, “like it”, “it’s okay”, “dislike it”, and “hate it”, and a slider allowing a continuous rating from ±100.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participation in physical activity is associated with a better body size perception but not in a consistent way. In this line, Hubert et al [ 12 ] reported that collegiate women ( n = 251; 74% white), who perceived greater body size, reported less liking of physical activity as well as less healthy dietary behaviours. Additionally, women whom both liked and engaged in physical activities had a lower body size perception and healthier diet quality.…”
mentioning
confidence: 99%